2021
DOI: 10.3390/antibiotics10101258
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of a Novel 1,2,4-oxadiazole-containing Derivative with Oxacillin against Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcusaureus is an important opportunistic pathogen that causes many infections in humans and animals. The inappropriate use of antibiotics has favored the diffusion of methicillin-resistant S. aureus (MRSA), nullifying the efforts undertaken in the discovery of antimicrobial agents. Oxadiazole heterocycles represent privileged scaffolds for the development of new drugs because of their unique bioisosteric properties, easy synthesis, and therapeutic potential. A vast number of oxadiazole-containing der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The minimal inhibitory concentration (MIC) of all the compounds was determined in Mueller-Hinton medium (MH) by the broth microdilution assay, following the procedure already described (Buommino et al, 2021). The compounds were added to bacterial suspension in each well, yielding a final cell concentration of 1 × 10 6 CFU/mL and a final compound concentration ranging from 3.25 to 100 μM.…”
Section: Bacteria Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…The minimal inhibitory concentration (MIC) of all the compounds was determined in Mueller-Hinton medium (MH) by the broth microdilution assay, following the procedure already described (Buommino et al, 2021). The compounds were added to bacterial suspension in each well, yielding a final cell concentration of 1 × 10 6 CFU/mL and a final compound concentration ranging from 3.25 to 100 μM.…”
Section: Bacteria Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…In a recent report, Yadav and Ganguly et al [141,144] mention that a novel quinazolinone-based small molecule was found to have an inhibitory activity that was as effective as non-β-lactam antibiotics towards the MRSA pathogen by possibly targeting the PBP2a leading to the inhibition of the cell wall synthesis. The bioisosteric modifications of lead molecules helped in the retention of pharmacophoric features and led to novel quinazolinone derivative pyrazole and benzimidazole-based small molecules.…”
Section: Novel Pyrazole-benzimidazole Based Derivativesmentioning
confidence: 99%
“…In drug discovery, benzimidazoles are heterocyclic ring systems that have attracted numerous researchers worldwide due to their therapeutic potential [144]. The benzimidazole nucleus is essential in lead discovery.…”
Section: Novel Pyrazole-benzimidazole Based Derivativesmentioning
confidence: 99%
“…[9] A vast number of 1,2,4-oxadiazole-bearing molecules have been found to possess diverse biological activities, such as anticancer, anti-inflammatory, anticonvulsant, antiviral, antibacterial, and anti-Alzheimer activities, as well as specific inhibitory properties against enzymes. [10] The first in class commercial drug containing 1,2,4-oxadiazole ring Oxolamine was introduced as a cough depressant in the market. [8] Besides the enormous biological potential of oxadiazole derivatives in order to get better antibacterial motifs, we selected sulfonamide functionality.…”
Section: Introductionmentioning
confidence: 99%